INFLUENCE OF INDIVIDUAL AND SYNERGISTIC ADDITION OF MORINGA OLEIFERA SEEDS AND LEAVES POWDER TO BROILER DIETS ON GROWTH PERFORMANCE - Al-Khafaji , M. S. L.; Al-Hammed, S. A. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted at the poultry farm\Abu Ghraib, College of Agricultural Engineering Sciences, University of Baghdad, for the period from 12-10-2022 to 22-11-2022 lasted for 42 days to study the effect of individual and synergistic addition of Moringa oleifera seeds and leaves powder to broiler diets on growth performance. 210 one day old unsexed broiler chicks (Ross-308), randomly distributed in to seven treatments with three replicates per treatment and 10 chicks per replicate as follows: T1 (control treatment) without additive, T2: 1% seeds powder, T3: 2% seeds powder, T4: 1% leaves powder, T5:  2% leaves powder, T6: 0.5% seeds powder + 0.5 leaves powder, T7: 1% seeds powder + 1% leaves powder. The results indicated a significant superiority (P≤0.05) for the T4 treatment in the average live body weight and weight gain compared to control treatment T1 at the first week, as well as the T1 and T4 outperformed the T3 in the same trait at the fourth week, and the T4 recorded a significant superiority in the amount of feed consumed compared to control treatment T1 and T3 at the first week. Also, the T1 and T2, followed by T4, outperformed the rest of the other treatments in the average of feed consumption at the sixth week, while no significant differences appeared between all the treatments in the feed conversion throughout the experiment period. Based on the results of this study, it is concluded that the addition of Moringa seed and leaf powder did not have a significant effect on cumulative growth performance, and it is considered safe at the levels used.